Mutu Benih Jagung ( Zea Mays L. ) yang Disimpan dengan Drum dan Silo pada Masa Simpan 0, 1 dan 2 Tahun - GAMA, FRANSISCO FILIPE; ASTININGSIH, ANAK AGUNG MADE; RAKA, I GUSTI NGURAH (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.6, No.4, Oktober 2017, 2017)
Effect of Seed Storage with Drum and Silo on the Shelf Life of 0, 1, and 2 Years on the Seed Quality of Corn (Zea mays L.) This study aims to determine the effect of seed storage with drum and silo on the shelf life of 0, 1, and 2 years on the seed quality of corn (Zea mays L) varieties sele. This study uses a completely randomized design (CRD) consisting of 6 treatments and 5 replications. The treatment is sixth with a storage drum storage period of 0, 1, and 2 years (DT0, DT1.DT2) and storage silo storage period of 0, 1, and 2 years (ST0, ST1, ST2). The observed variables include moisture content, germination, germination synchrony, seedling dry weight, and the growing strength. The results showed that the seed moisture content decreased with the longer shelf life of both the drum and silo storage. Likewise, other variables, such as germination, simultaneity of germination, seedling dry weight and strength grew. All of these variables are impaired by the longer storage of both the drum and the silo. Storage for one year either in drums or silos are still able to maintain the quality of seed corn above the standard, with over 80% germination.